2017
DOI: 10.1186/s12931-017-0529-6
|View full text |Cite
|
Sign up to set email alerts
|

Combination of glycopyrronium and indacaterol inhibits carbachol-induced ERK5 signal in fibrotic processes

Abstract: BackgroundAirway fibrosis is one of the pathological features of chronic obstructive pulmonary disease (COPD), and recent studies revealed that acetylcholine plays an important role in the development of airway remodeling by stimulating proliferation and collagen synthesis of lung fibroblasts. This study was designed to examine the effects of a long-acting muscarinic receptor antagonist (LAMA) glycopyrronium and a long-acting β2 adrenergic receptor agonist (LABA) indacaterol on acetylcholine-mediated fibrotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
3
0
1
Order By: Relevance
“…In conclusion, the results presented here provide evidence of the high sensitivity of fibrotic fibroblasts to the canonical TGF-β1/Smad3 signaling pathway, which mediates fibrotic processes that can be suppressed by ERK5 inhibitor treatment; this extends our previous findings that ERK5 inhibitor suppressed airway fibrosis in COPD lung fibroblasts [12]. The screened genes and TGF-β1-ERK5 interaction analysis provide detailed insights into the molecular mechanism underlying the progression of lung fibrosis mediated by fibrotic fibroblasts.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In conclusion, the results presented here provide evidence of the high sensitivity of fibrotic fibroblasts to the canonical TGF-β1/Smad3 signaling pathway, which mediates fibrotic processes that can be suppressed by ERK5 inhibitor treatment; this extends our previous findings that ERK5 inhibitor suppressed airway fibrosis in COPD lung fibroblasts [12]. The screened genes and TGF-β1-ERK5 interaction analysis provide detailed insights into the molecular mechanism underlying the progression of lung fibrosis mediated by fibrotic fibroblasts.…”
Section: Discussionsupporting
confidence: 83%
“…BIX02189, a pharmacological inhibitor of MAPK kinase 5/ERK5, blocked TGF-β signaling and subsequent profibrogenic responses in a bleomycin-induced lung fibrosis model [11]. We previously demonstrated that BIX02189 attenuates acetylcholine and TGF-β1-mediated ERK5 signaling, reducing the contractility of lung fibroblasts present in clinical samples from patients with chronic obstructive pulmonary disease (COPD), which suggests prevention of airway remodeling [12].…”
Section: Introductionmentioning
confidence: 99%
“…The two wells of the Boyden blind well chamber were separated by an 8-μM pore filter (Nucleopore, Pleasanton, CA, USA). The chambers were incubated at 37 °C in a humid atmosphere containing 5% CO 2 for 8 h, after which the cells on top of the filter were removed by scraping [8, 11, 23]. The cells that had migrated through the filter were then fixed, stained with DiffQuick Sysmex (16920), and mounted on glass microscope slides.…”
Section: Methodsmentioning
confidence: 99%
“…Показано, что терапия с использованием фиксированной комбинации индакатерол (ИНД)/гликопирроний (ГЛИ) может предотвратить «клинически значимое ухудшение» ХОБЛ на 28% по сравнению с тиотропием и на 33% по сравнению с ИГКС/ДДБА («клинически значимое ухудшение ХОБЛ» определяется временем/риском развития одного из изменений: снижение объема форсированного выдоха за 1-ю секунду (ОФВ 1 ) ≥100 мл, ухудшение показателя SGRQ ≥4 баллов, CAT ≥2 баллов, TDI ≥1 балла, возникновение умеренных /тяжелых обострений) [13]. Подтверждена способность ИНД/ГЛИ in vitro предупреждать развитие ремоделирования бронхов и перибронхиального фиброза на ранних стадиях ХОБЛ [14]. Таким образом, ДДБА/ДДАХ -наиболее эффективная медикаментозная терапия для достижения и поддержания контроля как симптомов, так и риска обострений у большинства пациентов с ХОБЛ [при отсутствии сопутствующей БА и выраженной эозинофилии (ЭОЗ) в крови].…”
Section: сн авдеев и соавтunclassified